The event of postcolonial shame - Bewes, Timothy (Princeton, N.J. : Princeton University Press, 2011)
Argues that shame is a dominant temperament in twentieth-century literature, and the key to understanding the ethics and aesthetics of the contemporary world. This title states that the practices of postcolonial literature depend upon and repeat the same structures of thought and perception that made colonialism possible in the first place.
Acknowledgments ix Prologue 1 Part One: The Form of Shame Chapter One: Shame as Form 11 Form and Disjunction: A Recent History 15 Primo Levi's The Drowned and the Saved 20 Three Preliminary Theses 23 Postcolonial Shame and the Novel 41 Chapter Two: Shame, Ventriloquy, and the Problem of the Cliche: Caryl Phillips 49 Precipitation of Shame 53 The Materiality of Postcolonial Shame 56 Cambridge and Crossing the River 61 The Poetics of Impossibility 66 Part Two: The Time of Shame Chapter Three: The Shame of Belatedness: Late Style in V. S. Naipaul 75 Being and Belatedness 78 Late Style in Adorno 82 Liber solemnis: The Enigma of Arrival 87 Crystal of Shame: The Mimic Men 94 Chapter Four: Shame and Revolutionary Betrayal: Joseph Conrad, Ngugi wa Thiong'o, Zoe Wicomb 100 Hegel: Text as Antitext 103 Joseph Conrad: Form as the Evacuation of Form 108 Ngugi wa Thiong'o: The Imminence of Betrayal 115 Zoe Wicomb: The Difference of the Same 123 Alain Badiou: Subtraction versus Realization 128 Part Three: The Event of Shame Chapter Five: The Event of Shame in J. M. Coetzee 137 The Problem of "Agency" 138 Two Shames in Coetzee 142 Diary of a Bad Year 146 The New Direction 150 Positively White: Slow Man and Corporeal Shame 153 Chapter Six: Shame and Subtraction: Towards Postcolonial Writing 164 The Origins of This Book: Michel Leiris 167 Deleuze and Sartre 169 Subtraction 173 Louis Malle's L'Inde fantome 178 Towards Postcolonial Writing 187 Notes 193 Index 219
Includes bibliographical references (pages [193]-218) and index.
ENH
Keywords: Commonwealth literature (English) -- History and criticism; Postcolonialism in literature; English literature